The Effectiness of Train to Train Game in The Improvement of Speaking Skills of English Course Students: A Case Study at Ef Tanjung Duren - Muhartoyo Muhartoyo; Meilina Meilina (Bina Nusantara University, 2011)
Article clarifies on how the students’ speaking abilities can be stimulated by Train to Train game. The writers create Train to Train game which covers three activities, those are drawing, explaining, and making chain story that can be done individually and also in a team. Twenty-four students have participated in this research and the writers use Train to Train game as an experimental tool in the class for forty-five minutes in each meeting. The writers collect the data from eight meetings inside the classroom twice a week in each class. The beneficial impact of the Train to Train game is evaluated by comparing the results of the pre-test and post-test. The questionnaires distributed to the students is used to obtain insights/ feedback from the students The result of the research proves that Train to Train game can stimulate the students to speak English more confidently, clearly, corectly, and fluently than before they practice the game.